Analysis of Micro, Small and Medium Enterprises (MSMES) Based on Modern Islamic Boarding Schools in East Jakarta - Dwi Sulastri (Green Publisher Indonesia, 2024)
Ibnu Hajar Boarding School (IHBS), a modern Islamic boarding school in East Jakarta, combines classical Islamic education with a modern approach to meet the needs of the era of globalization. This research aims to understand education management in IHBS, identify obstacles, solutions, and future development plans. Data was collected through interviews with decision-makers at Islamic boarding schools, including caregivers, internal supervisors, principals, and managerial staff. The results of the study show that education management at IHBS has included planning, organizing, managing human resources, directing, and supervising. However, implementation still needs improvement. Factors supporting success include the support of the entire IHBS community, adequate facilities, managerial openness, and good financial management. Meanwhile, inhibiting factors include differences in perception between employees, incomplete SOPs, lack of human resource competence, and lack of focus in management and regeneration. In addition to education, IHBS also manages MSMEs consisting of mini markets, catering, laundry, convection, cafes, and refillable water. Despite playing an important role in the pesantren economy, several obstacles are still faced, such as contracts that are not yet shallow, business stagnation, and the lack of professionalism of human resources relevant to business demands.